A study on flexural modulus and ductility of laminated cementitious composites - Hossain, M. Z. (Universiti Teknologi Malaysia, Fakulti Kejuruteraan Awam, 2010)
This paper presents a new approach for flexural modulus of laminated composites derived from the analysis of a flexural-section composed of several ductile and brittle layers of different moduli. The derivation is based on the assumption that the tension and compression zones of the laminated composite are symmetrical with respect to the neutral axis and thus, half of the section is needed to analyze for complete derivation of flexural modulus of the whole section. This composed of two ductile layers of higher moduli providing in both tension and compression zones to maintain the equilibrium conditions during flexure. The formulation shows that the flexural modulus of the entire section of laminated composites obtained by this method is equal to the modulus of ductile layers plus a factor of the difference of modulus of ductile and brittle layers. It is concluded that this factor is different from the usual one which is obtained under uniaxial loadings. Despite the fragile nature of brittle layers of the composite, it has been found that the inclusion of two ductile layers into the laminated cementitious composites makes it fully ductile material owing to the synergetic action between the layers of two components.